Violations of Forestry Legislation and Their Enforcement in Mining Ural Region during 1870s to Early 1890s - D. Yu. Pukhov (Научный диалог, 2024)
This study examines the dynamics, social dimensions, causes, and characteristics of illegal activities within the forestry sector of the Mining Ural region from the 1870s to the early 1890s, focusing on data from the Perm Province. The analysis reveals a high incidence of crimes related to the theft and damage of timber resources, supported by identified statistical data. It is shown that the increasing trend of such offenses prompted a tightening of state law enforcement policies during the reign of Alexander III. Notably, the most serious crimes in the forestry sector, which fell under the jurisdiction of general judicial institutions — such as mass resistance against forest guards and armed threats to officials of the mining and forestry agency—were relatively rare. This study provides a novel analysis of the class, gender, and age structure of individuals convicted for violations of state forest regulations. At the micro level, it highlights the realities of forestry crime and its suppression in the Ural region. Based on materials from periodicals, administrative records, and judicial investigation documents, it concludes that the prevalence of timber theft in the Mining Ural region stemmed from unresolved issues in state regulation of forestry relations and other problems, including unemployment, poverty, and inaccessibility to essential resources. The author argues that a significant portion of forestry law violations in the Ural region during the late 19th century can be characterized as social crime.